Design of the strategy and architecture of different enterprises’ middle platform - Yinghui LIU; Nan LIU; Yixin CAI; Yunyong ZHANG; Jinwu WEI (Dianxin kexue)
With the national economic transition and rapid development of technology,enterprises need digital transition.How to accelerate transition through IT architecture upgrading has become a new research topic for enterprises.The definition,function and common types of middle platforms were stated.The strategy and architecture of different enterprises’ middle platforms which differ in service chain length were also compared and analyzed.The concept of planning middle platform was proposed on the basis of decoupling production from operation.Considering the current situation of operators,some suggestions were put forward on how to design the middle platform and which type to choose.